Aerophagia Study in Indonesia: Prevalence and Association With Family-related Stress. Issue 9 (October 2021) - Oswari, Hanifah; Alatas, Fatima S.; Hegar, Badriul; Cheng, William; Pramadyani, Arnesya; Benninga, Marc A.; Rajindrajith, Shaman
Abstract : Background: Aerophagia is a functional gastrointestinal disorder characterized by repeated air swallowing leading to chronic abdominal distension. Symptoms can be long lasting, lead to frustration, and distress. This study describes prevalence, related factors, and symptomatology of aerophagia, together with its relationship with emotional stress. Materials and Methods: Cross-sectional study. Adolescents aged 10 to 17 years from selected state schools by convenient sampling from Jakarta, Indonesia, were recruited. Rome III self-administered questionnaire was used to compile data on gastrointestinal symptoms. Data on sociodemographic characteristics, intestinal and extraintestinal symptoms, and stressful life events were collected using a separate questionnaire. Results: A total of 1796 questionnaires were included in the analysis [males 732 (40.8%), mean age 13.58 (SD 0.992) years]. There were 81 (4.5%) subjects diagnosed with aerophagia. When the criterion of belching was removed from the diagnosis of aerophagia, the prevalence drops to only 2 (0.1%). subjects. Bivariate analysis showed that sociodemographic factors have no correlation with aerophagia. In subjects with aerophagia, among the intestinal-related and extraintestinal symptoms, only loss of appetite was significantly more common in the aerophagia population (33.3%) when compared with controls (22.8%). Death of a close family member [adjusted odds ratio (OR), 2.78; 95% confidence interval (CI), 1.46-5.31; P =0.002], divorce or separation of parents (adjusted OR, 2.54; 95% CI, 1.38-4.66; P =0.003), and divorce followed by separate individual remarriage of parents (adjusted OR, 2.01; 95% CI, 1.01-3.98; P =0.046) were found to be significantly associated with aerophagia by multivariate analysis. Conclusions: The prevalence of aerophagia was found in 4.5% of Indonesian school-aged children according to Rome III criteria, but the prevalence was found only 0.1% if the belching is removed from the criteria. Besides the main symptoms, only loss of appetite was significantly more common in aerophagia among intestinal-related and extraintestinal symptoms. Family-related stress showed a significant correlation with aerophagia.